Papua New Guinea Teachers : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2015)
This report presents results of the application of SABER teachers in Papua New Guinea. It describes Papua New Guinea’s performance in each of the eight teacher policy goals, alongside comparative information on education systems that have consistently scored highly on international student achievement tests and have participated in SABER-Teachers. Additional detailed descriptive information on the teachers policies of the education systems of Papua New Guinea and other education systems can be found on the SABER-teachers website.